2020
DOI: 10.1002/htj.22020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of U‐shaped serpentine microchannel heat sink using various metal oxide nanofluids

Abstract: This study aims to evaluate the thermal performance and friction factor characteristics of the U‐shaped serpentine microchannel heat sink using three different nanofluids. Two distinct nanoparticles, namely Al2O3 (alumina) and CuO (copper oxide), were used for the preparation of nanofluids using water and ethylene glycol (EG) as base fluids. Three nanofluids, namely nanofluid I (Al2O3 + water), nanofluid II (CuO + water), and nanofluid III (CuO + EG), have been prepared. The results showed that the thermal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Noctanol has been discovered to have improved fuel characteristics for CI engines when compared to ethanol and butanol. The CN for n-octanol is 39, which is significantly higher than the CN for n-butanol (17) and ethanol (11) but slightly lower than the CN for diesel fuel (45−50). The increased heating value of noctanol (LHV = 37.5−38.4 MJ/kg vs ethanol (21.4−26.9 MJ/ kg) and butanol (26.9−36.0 MJ/kg) for CI engines is another key property.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Noctanol has been discovered to have improved fuel characteristics for CI engines when compared to ethanol and butanol. The CN for n-octanol is 39, which is significantly higher than the CN for n-butanol (17) and ethanol (11) but slightly lower than the CN for diesel fuel (45−50). The increased heating value of noctanol (LHV = 37.5−38.4 MJ/kg vs ethanol (21.4−26.9 MJ/ kg) and butanol (26.9−36.0 MJ/kg) for CI engines is another key property.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, while the alcohol-diesel mixes greatly lower smoke and particulate emissions, the effects of other gases are affected by a range of parameters, including engine supply systems, exhaust control measures, and engine test processes. The automobile sector is confronted with significant problems, including the need for better engines, drive train electrification, and the substitution of fossil fuels with alternatives to reduce greenhouse gas emissions. As a result, fuel and engine technologies have a twin challenge in lowering fuel usage and greenhouse gas emissions. In this situation, novel concepts and efficient combustion procedures are increasingly relevant, such as enhanced spray atomization, A/F mixing, lower local equivalence ratios, lower peak temperature inside the combustion cylinder, and higher combustion rates. Alcohol fuels have been determined to be a promising alternative to fossil fuels with fewer emissions when modern combustion technologies are applied. Figure shows the production techniques for various alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are proposed to analyse the stability of nanoparticles in the samples, including sedimentation, centrifugation, zeta potential and spectral absorbency techniques. 30 Here, the sedimentation technique was applied to study the stability of the prepared fuel blends.…”
Section: Methodsmentioning
confidence: 99%
“…It improves heat transfer characteristics with slight pressure drop. Sivakumar et al [9] investigated the use of various metal oxide nanofluids Al 2 O 3 + water, CuO + water, and CuO + EG in U-shaped serpentine microchannel heat sink. The founding showed that the thermal conductivity of nanofluids was increased for all concentrations (from 0.01 to 0.3% volume), compared with base fluids.…”
Section: Introductionmentioning
confidence: 99%